2014
DOI: 10.1103/physrevb.89.081108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spin fluctuations on quasiparticle excitations: First-principles theory and application to sodium and lithium

Abstract: We present first-principles calculations for quasiparticle excitations in sodium and lithium including the effects of charge and spin fluctuations. We employ the Overhauser-Kukkonen form for the electron self energy arising from spin fluctuations and demonstrate that the coupling of electrons to spin fluctuations gives an important contribution to the quasiparticle lifetime, but does not significantly reduce the occupied bandwidth. Including correlation effects beyond the random-phase approximation in the scre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
35
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 42 publications
4
35
1
Order By: Relevance
“…1 Interestingly, the experimental result agrees quite well with the bandwidth from a LDA+GW xc calculation, 11,31 which contains vertex corrections for the dielectric function; however, including vertex corrections also in the self-energy increases the bandwidth again. [54][55][56] As an alternative explanation, Shung and Mahan 57,58 suggested that the measured bandwidth results from many-body effects in combination with final-state effects and an interference between surface and bulk photoemission.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…1 Interestingly, the experimental result agrees quite well with the bandwidth from a LDA+GW xc calculation, 11,31 which contains vertex corrections for the dielectric function; however, including vertex corrections also in the self-energy increases the bandwidth again. [54][55][56] As an alternative explanation, Shung and Mahan 57,58 suggested that the measured bandwidth results from many-body effects in combination with final-state effects and an interference between surface and bulk photoemission.…”
Section: Resultssupporting
confidence: 55%
“…G 0 W 0 ) calculations 2,3 where screening is treated in the random-phase approximation, as well as G 0 W xc calculations where screening is treated with the DFT-LDA dielectric function. 11,31 We also evaluate spectral functions using the GW-plus-cumulant (henceforth GW+C) method. This approximation yields the exact solution for a dispersionless core electron interacting with plasmons 32 and noticeably improves the description of plasmon satellite properties compared to GW, while retaining the accuracy of GW for the quasiparticle energies.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, there is a need for a fully first-principles theory without empirical parameters. We have recently developed such an ab initio theory [15] for the spin fluctuation-electron coupling based on the work of Overhauser and coworkers on the homogeneous electron gas [16,17].…”
mentioning
confidence: 99%
“…The effective spin-fluctuation mediated interaction is obtained using a recently developed first-principles formalism [15,19] based on the work of Overhauser et al for the homogeneous electron gas [16,17]. In this approach, the effective interaction is expressed as the sum of a bare Coulomb interaction, a contribution arising from charge fluctuations and a contribution arising from spin fluctuations, which is given by…”
mentioning
confidence: 99%
“…In fact, in going from continuous to discrete translational symmetry the functions simply turn into matrix functions [e.g., Σðk; ωÞ → Σ GG 0 ðk; ωÞ], something that does not pose any conceptual difficulties for Monte Carlo momentum integration [85]. Alkali metals for which a vertex function has been partially included (typically using a model exchange-correlation kernel [87,88]) are a logical next step for our method. It is conceivable that higher order satellites can be accurately described by the combination of our approach with the cumulant expansion scheme outlined in Refs.…”
mentioning
confidence: 99%